Use of Phase-Contrast MRA to Assess Intracranial Venous Sinus Resistance to Drainage in Healthy Individuals - Fall, S.; Pagé, G.; Bettoni, J.; Bouzerar, R.; Balédent, O. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Resistance to blood flow in the cerebral drainage system may affect cerebral hemodynamics. The objective of the present study was to use phase-contrast MRA to quantify resistance to drainage of blood across branches of the venous sinus tree and to determine whether the resistance to drainage values correlated with internal jugular vein outflows.MATERIALS AND METHODS: We performed whole-head phase-contrast MRA and 2D phase-contrast MR imaging in 31 healthy volunteers. Vascular segmentation was applied to the angiograms, and the internal jugular vein velocities were quantified from the flow images. Resistance to drainage across branches of the venous sinus tree was calculated from the segmented angiograms, by using the Poiseuille equation for laminar flow. Correlations between the values of resistance to drainage and internal jugular vein outflow measurements were assessed by using the Spearman ρ.RESULTS: The overall mean resistance to drainage of the venous sinus tree was 24 ± 7 Pa s/cm3. The mean resistance to drainage of the right side of the venous sinus tree was 42% lower than that of the left side (P < .001). There were negative correlations between the values of resistance to drainage and internal jugular vein outflows on both the left side of the venous sinus tree (R = −0.551, P = .002) and the right side (R = −0.662, P < .001).CONCLUSIONS: Phase-contrast MRA is a noninvasive means of calculating the resistance to drainage of blood across the venous sinus tree. Our approach for resistance to drainage quantification may be of value in understanding alterations in the cerebral venous sinus drainage system.AIasymmetry indexIJVinternal jugular veinPC-MRAphase-contrast MR angiographyRdresistance to drainage